2018
DOI: 10.1128/iai.00172-18
|View full text |Cite
|
Sign up to set email alerts
|

The Ethanolamine Permease EutH Promotes Vacuole Adaptation of Salmonella enterica and Listeria monocytogenes during Macrophage Infection

Abstract: Ethanolamine is a ubiquitous and essential molecule within a host. Significantly, bacterial pathogens exploit ethanolamine during infection to promote growth and regulate virulence. The ethanolamine permease EutH is dispensable for growth under standard conditions, whereas EutH is required for ethanolamine utilization at low pH. These findings suggested a model in which EutH facilitates diffusion of ethanolamine into the bacterial cell in acidic environments. To date, the ecological significance of this model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 80 publications
(102 reference statements)
0
26
0
Order By: Relevance
“…EA utilization plays a central role in host adaptation for a diverse range of pathogens, including opportunistic pathogens ( 3 , 4 ). EA can serve as a carbon, nitrogen, and/or energy source to promote growth as well as a signal to influence virulence during host infection ( 5 11 ). Genes encoding EA utilization are carried in the e thanolamine ut ilization ( eut ) locus ( 12 ).…”
Section: Observationmentioning
confidence: 99%
“…EA utilization plays a central role in host adaptation for a diverse range of pathogens, including opportunistic pathogens ( 3 , 4 ). EA can serve as a carbon, nitrogen, and/or energy source to promote growth as well as a signal to influence virulence during host infection ( 5 11 ). Genes encoding EA utilization are carried in the e thanolamine ut ilization ( eut ) locus ( 12 ).…”
Section: Observationmentioning
confidence: 99%
“…Some bacteria also sense ethanolamine outside of the GI tract to regulate gene expression [44,[59][60][61][62]. In addition, previous studies have demonstrated that ethanolamine utilization can both positively and negatively affect host colonization and virulence during infection [44,46,55,[59][60][61][62][63]. We and others [47], showed that certain Vibrios are unable to metabolize ethanolamine as either carbon or nitrogen source, nevertheless, the influence of ethanolamine on virulence gene expression can be independent of ethanolamine metabolism [44,57].…”
Section: Discussionmentioning
confidence: 89%
“…Although we cannot rule out molecules present in the GI tract other than ethanolamine can also act on CqsR, other enteric pathogens including E. coli, Salmonella, Enterococcus, and C. difficile have adopted different mechanisms to sense this common metabolite to regulate their gene expression to improve their fitness inside the host [44,46,[55][56][57][58]. Some bacteria also sense ethanolamine outside of the GI tract to regulate gene expression [44,[59][60][61][62]. In addition, previous studies have demonstrated that ethanolamine utilization can both positively and negatively affect host colonization and virulence during infection [44,46,55,[59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of L. monocytogenes cells remains confined to the phagosome 2-3 h post-infection (de Chastellier and Berche, 1994;Singh et al, 2008). Anderson et al (2018) also proposed that there may be a functional link between LLO and EutH; however, a hypothesis that suggests a function was not proposed in the study. These findings highlight the importance of EutH for the survival and replication of L. monocytogenes in macrophages in response to vacuole acidification.…”
Section: Virulencementioning
confidence: 89%
“…However, EA is protonated in acid conditions and requires the EA permease, EutH, to be internalized by L. monocytogenes. Anderson et al (2018) elucidated that EutH is important for the intracellular survival and replication of S. Typhimurium and L. monocytogenes. EutH did not promote intestinal infection but instead provides a crucial advantage in the dissemination of L. monocytogenes to the liver and spleen.…”
Section: Virulencementioning
confidence: 99%